Os crimes do colarinho branco na perspectiva da sociologia criminal - Veras, Ryanna Pala (2006)
This work analises, in the sociological macro level, which perspective should be applied to study white collar crimes in criminology. The sistematic study of crime has begun in the beginning of the XVIII century with the Classic School, however, it has been in the end of the XIX century that emerged the sociologycal studies of crime, influenced by the works of Durkheim. In the beginning of the XX century, sociology has turned an universitary discipline, in the University of Chicago, where has been developped the first sociologycal theory of crime, the Chicago School. Then, the sociology has been divided in two distinct levels, the micro level sociology, which studies the interaction between society and man, and the macro level, which studies the society's structure. The term white collar crime was criated by the american sociologist Edwin Sutherland, in 1939. For him, white collar crime is that one commited by respectable person from the high social class, in his business. Sutherland noted that the punishment of these crimes was less commom than the punishment of the ordinary crimes. The macro level theories which considered this question were the anomie theory, labeling approach, conflict criminology and critical criminology. The first one has analised the theme in the etiologic perspective and the others has used the perspective of social reaction. The etiologic perspective intends to find an ontologic substract in crime and reveal its causes. The perspective of social reaction considers the crime a criation of the criminal system, by the selection of actions, interpretation and a final definition in a judicial sentence. This work intends to demonstrate that the study of white collar crimes should addopt the social reaction perspective, because, it should answer in first place the question: why the white collar crimes are not absorved by the criminal system? As it's impossible to obtain some reliable sample to develop etiologic studies if the real forces that control the penal system and the society were not revealed